Capela do Rio do Peixe em Pirenópolis/Goiás: lugar de festa - Lôbo, Tereza Caroline (2011)
The celebration in honor of Our Lady of St. Ana which occurs since the eighteenth century, in July, in the Capela do Rio do Peixe in Pirenópolis/GO, constitutes a phenomenon characteristic of the community who have experienced it, implying as a process that involves action and production of a place clearly buoyed by moments of sharing and solidarity. This "meeting place" is tied to space and landscape, and these shares are essential in the formation of identities and manifestations of the place. It is proposed in this paper a research focus, through symbols and rituals at the party-place, the meanings of this phenomenon festive. The research aims to highlight that more than an ancient religious tradition, festive resistant to change and the party conflict is revealed as a phenomenon based on an intense self-managed process, the original party disappeared and transcended the religious aspect, and now presents different uses and meanings. Thus, we sought the possible answers to the problem proposed in this study, namely: how the conflicts arising from the encounter of several trajectories during the time of the party appear in our present and guide the senses of place given to them (the participants ) to the feast of Our Lady at St. Ana's Capela do Rio do Peixe, Pirenópolis/GO? In conducting the research at the present time (2007 to 2010) and live with / in their area of occurrence is proposed to submit more than one outside world in importance and power that provides a simple environment of human action, but an inner world, feelings and desires that impresses by the complexity of their reality.